IS THEOLOGY RESPECTABLE AS METAPHYSICS? - Jones, Nicholaos (Zygon: Journal of Religion & Science, 2008)
Theology involves inquiry into God's nature, God's purposes, and whether certain experiences or pronouncements come From God. These inquiries are metaphysical, part of theology's concern with the veridicality of signs and realities that are independent from humans. Several research programs concerned with the relation between theology and science aim to secure theology's intellectual standing as a metaphysical discipline by showing that it satisfies criteria that make modern science reputable, on the grounds that modern science embodies contemporary canons of respectability for metaphysical disciplines. But, no matter the ways in which theology qua metaphysics is shown to resemble modern science, these research programs seem destined for failure. For, given the currently dominant approaches to understanding modern scientific epistemology, theological reasoning is crucially dissimilar to modern scientific reasoning in that it treats the existence of God as a certainty immune to refutation. Barring the development of an epistemology of modern science that is amenable to theology, theology as metaphysics is intellectually disreputable.